Clinical Characteristics of Osteoarthritic Patients with and Without Calcium Pyrophosphate Deposition Disease Who Underwent Total Knee Arthroplasty at Nongkhai Hospital - ติณหภัทร, จินตาหรา (Journal of Health Science of Thailand, 2024)
Osteoarthritis and calcium pyrophosphate deposition disease are common in the elderly. In some studies, osteoarthritic patients with calcium pyrophosphate deposition disease often have more severe symptoms and disability than primary osteoarthritic patients. However, the diagnosis and treatment of these diseases are still difficult and based on the types or signs and symptoms of the patients. This descriptive study aimed to determine the clinical characteristic and the factors related to the characteristics of osteoarthritic patients with and without calcium pyrophosphate deposition disease who underwent total knee arthroplasty at Nongkhai Hospital between 2020-2023. The qualitative data were analyzed by Chi-square test or Fisher’s exact test, and the quantitative data were analyzed by Unpaired t-test or Mann-Whitney U test. Of the 164 eligible patients, 32.9% of them were osteoarthritic patients with calcium pyrophosphate deposition disease. From the current study, osteoarthritic patients with calcium pyrophosphate deposition disease were often found with diabetes mellitus, hypertension, dyslipidemia, and chronic kidney disease; and the median age and duration of symptoms were significantly longer than osteoarthritic patients without calcium pyrophosphate deposition disease (p<0.05). Furthermore, osteoarthritic patients with calcium pyrophosphate deposition disease were more likely to be inflamed and required more nonsteroidal anti-inflammatory drugs (94.4% and 91.8% respectively, p=0.544, OR=1.515), In summary, osteoarthritic patients should always be evaluated for calcium pyrophosphate deposition disease because they were more likely to be inflamed and had a longer duration of symptoms. They might require different assessment and treatment adjustments than those without calcium pyrophosphate deposition disease.